The Influence Of Economic Status In The Selection Of Iud Contraceptive Devices In Sengkol Public Health Center, Pujut District, District Central Lombok - Dina Mariana; Nita Dwi Astikasari; Donny Irawan (Journal of Health Science Community, 2023)
According to the World Health Organization (WHO), family planning is an attempt to measure the number and distance of children desired. In order to achieve this, several ways or alternatives are made to prevent or delay pregnancy. These include contraception or pregnancy prevention and family planning (WHO, 2016). Based on the results of interviews with the coordination midwife at the Sengkol Public Health Center, a survey data of 15 people showed that there were still many women who were not interested in using an IUD. The purpose of this study was to analyze the effect of economic status on the interest in choosing IUD contraceptives for family planning acceptors in the Sengkol Community Health Center in 2023. Based on the scope of the study, including the type of quantitative research with a correlation design, that is, it only connects between research variables with cross-sectional research. The research was the Sengkol Community Health Center with the population in this study were all breastfeeding mothers who visited the Sengkol Community Health Center in 2023 with samples taken using the Sampling Purposive Sampling technique, total of 22 respondents. The independent variable in this study is economic status with an ordinal scale and the variable depending on the interest in choosing an IUD contraceptive device on an ordinal scale using a questionnaire research instrument that is distributed directly to respondents. In collecting data from respondents, was processing the data by editing, coding, scoring, tabulating, data entry, and cleaning. The data analysis in this study used the chi square test. In the chi square test analysis, it was found that p-value = 0.003 <α = 0.05 (p-value <α) which means that H0 is rejected and H1 is accepted, which means that there is an effect of economic status on maternal interest in IUD family planning.